ANALYSIS OF CURRENT TRENDS REVISION OF THE REQUIREMENTS FOR THE USE OF PSYCHOLOGICAL TESTS - Babajanyan, Irina (Modern Psychology, 2023)
This article aims to carry out an analysis of modern problems and requirements for the application of psychological assessment methods, which have been identified by scientists from various countries. The study does not pretend to be a mega-analysis, but considers contemporary articles from various scientific journals and educational books that have been published over the past five years. The presented analysis is of a comparative nature and indicates the specificity of approaches to the methods of psychological assessment and the degree of compliance with the basic requirements for their use in research and practice by psychologists from different countries. In the process of conducting a similar study, it is necessary to take into account modern challenges of a socio-psychological nature and changes in the conditions of research, counseling and therapy. In this regard, it was assumed that the recorded transformations influenced the form and format of obtaining a psychological diagnosis, namely: the meeting of the psychologist and the client in person or in absentia; filling out the test on a paper form or through a computer; using GOOGLE online forms for tests and surveys; and collection of testing metadata.